Comportamento assintótico dos autovalores de operadores integrais positivos via módulos de suavidade na esfera - Oliveira, Angelina Carrijo de (2015)
We study decay rates for eigenvalues of positive integral operators generated by kernels defined on the unit sphere Sm of the euclidean space Rm+1, m > 2, satisfying certain spherical conditions of smoothness, named Holder conditions and strong differentiability in the sense of Laplace-Beltrami.